Annual isotopic diet (δ13C, δ18O) of Notiomastodon platensis (Ameghino, 1888) from Brazilian Intertropical Region. (10th February 2022) - Dantas, Mário André Trindade; Liparini, Alexandre; Asevedo, Lidiane; França, Lucas de Melo; Cherkinsky, Alexander
Abstract: Notiomastodon platensis was an endemic South American proboscidean, which could reach about six tons and had a mixed feeder diet with predominance of C4 grasses in Brazilian Intertropical Region (BIR). In the last decades, its feeding behavior has been rebuilt mainly through dental calculus, enamel microwear and stable isotope analyses. However, all these techniques allow us to know only punctual information about its diet. In the present study we used stable isotopes (carbon and oxygen) in tusk fragments, allowing us to retrieve information about the six years of life for two individual specimens from Bahia state. The tusk fragment LGUESB 0002 was from an individual from Vitória da Conquista county, which lived at 17 ka BP and had a constant grazer diet in a stable climate environment. The other individual was from Coronel João Sá county that lived in the beginning of the Holocene at 9 ka BP, and presented a mixed feeder diet with consumption of C4 grass and C3 plants ( pi  = 40%), in an environment with high precipitation variation. This research presents the first annual series of isotopic composition for proboscidean tusks from BIR and the first evidence that the species lived in this region during the Holocene.